Effect of heat stress on mitogen-activated protein kinases in the hypothalamic–pituitary–gonadal axis of developing Wenchang chicks1 - Q.H. Li; Z.Q. Yu; Z. Chen (Poultry Science, 2020)
ABSTRACT: The regulatory roles of mitogen-activated protein kinase (MAPK) signaling pathways on the hypothalamic−pituitary−gonadal axis (HPG axis) of Wenchang chicks under heat stress (HS) were investigated. Additionally, the crosstalk between these signaling pathways was explored. Immunohistochemical experiments and Western blotting were employed to quantify extracellular regulated protein kinases (ERK), c-Jun N-terminal kinases (JNK), and p38MAPK (P38). In female chicks, hypothalamic ERKs were upregulated in Weeks 1 and 2 in the HS group compared with the control group (CK), while JNK and p38 were downregulated (P < 0.05). Pituitary MAPKs were all downregulated in the HS group compared with the CK group in Week 3, but p38 was upregulated in Week 4 (P < 0.01). In the HS group, ovarian MAPKs were all upregulated compared with the CK group during Week 5, whereas ERK was downregulated in Week 6 (P < 0.01). In contrast to the patterns of MAPK expression in female chicks in the HS and CK groups, ERK in male chicks showed a completely opposite pattern in Weeks 1, 2, and 5, while p38 and JNK were downregulated in both female and male chicks under HS during Weeks 2 and 3. In the HS group, pituitary and testis MAPKs showed a pattern opposite to that observed in female chicks under HS in Week 5; MAPKs were all downregulated (P < 0.05). Thus, there are gender differences in the MAPK signaling pathways in the HPG axis in chicks, and these pathways showed plasticity. Early HS can enhance chick growth and development as well as promote developing in the MAPK signaling pathways in the HPG axis. However, after heated brooding was discontinued in chicks, long-term HS obstructed chick development and caused tissue and function injury to the HPG axis.